2009
DOI: 10.1007/s10646-009-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bacterial diversity associated with metal-contaminated river sediments

Abstract: The temporal activity, abundance and diversity of microbial communities were evaluated across a metal-contamination gradient around a Superfund site in Montana. In order to analyze short-term variability, samples were collected from six sites on four occasions over 12 months. Measurements of community activity, diversity and richness, quantified by dehydrogenase activity and through denaturant gradient gel electrophoresis (DGGE), respectively, were higher at contaminated sites adjacent to the smelter, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 55 publications
5
58
0
2
Order By: Relevance
“…In the present study, bacterial community abundance and structure among four sites sampled during different seasons of the same year were explored by molecular and statistical analyses. The bacterial abundance was concurrent with that observed for other freshwater sediments ( Dorador et al, 2010;Jiang et al, 2007) , but lower than the typical range reported for sediment environments ( Bouskill et al, 2010;Eiler and Bertilsson, 2007) . The DGGE patterns suggested large numbers of bacterial species and high levels of bacterial diversity in river sediments, which was also confirmed by the Shannon-Weaver diversity index ( Bushaw-Newton et al, 2012;Cetecioǧlu et al, 2009 ) .…”
Section: Bacterial Communities In Jiaolai River Sedimentssupporting
confidence: 73%
“…In the present study, bacterial community abundance and structure among four sites sampled during different seasons of the same year were explored by molecular and statistical analyses. The bacterial abundance was concurrent with that observed for other freshwater sediments ( Dorador et al, 2010;Jiang et al, 2007) , but lower than the typical range reported for sediment environments ( Bouskill et al, 2010;Eiler and Bertilsson, 2007) . The DGGE patterns suggested large numbers of bacterial species and high levels of bacterial diversity in river sediments, which was also confirmed by the Shannon-Weaver diversity index ( Bushaw-Newton et al, 2012;Cetecioǧlu et al, 2009 ) .…”
Section: Bacterial Communities In Jiaolai River Sedimentssupporting
confidence: 73%
“…Earlier work shows that salinity and trace metals generate significant changes in microbial community composition (Baker and Banfield, 2003;Feris et al, 2003;Giller et al, 2009;Auguet et al, 2010;Lami et al, 2013). A number of studies have found that Cd and Zn in particular alter microbial community composition (Ganguly and Jana, 2002;Sverdrup et al, 2006;Bouskill et al, 2010;Xie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Beta-, Gamma-, and Epsilonproteobacteria were dominant in nitrate-treated sediments, while Firmicutes, Chloroflexi, and Deltaproteobacteria were dominant in the untreated sediments. Estimation of temporal bacterial diversity in the sediments of Clark Fork River, Montana, USA, a river exposed to complex mixtures of metals, by Bouskill and co-workers revealed a relatively stable, metal-tolerant community (Bouskill et al 2010). Predominant community members belonged to Beta-and Gammaproteobacteria, and statistically significant relationship between community composition and metals was established, indicating natural selection towards a metal-resistant microbial population.…”
Section: Surface Water Habitatsmentioning
confidence: 99%